A review of Ghana's water resource management and the future prospect. Issue 1 (31st December 2016) - Owusu, Phebe Asantewaa; Asumadu-Sarkodie, Samuel; Ameyo, Polycarp
Abstract: Water covers about 70% of the earth's surface and it exists naturally in the earth in all the three physical states of matter and it is always moving around because the water flows with the current. Out of the earth's percentage of water covering the surface, only about 2.5% is fresh water and due to the fact that most are stored in deep groundwater, a small amount is readily available for human use. Water scarcity is becoming a major concern for people around the world and the need to protect the existing ones and find ways or means to provide safe water for individuals around the globe in adequate quantities with keeping the needs of future generations in mind. Water is life, and it is linked with lots of services either directly or indirectly, such as; human health and welfare and social and economic development of a community or country. The need to delve into Ghana's water resources management is essential. The study reviewed existing literature on the various members of the Water Resource Commission (WRC) in Ghana; the various basins in the country; the existing measures that the WRC authorities have in place to deal with water resources management issues; the challenges that hinder the progress of their achievements and some suggestions that if considered can improve the current water resources management situations in Ghana.